(untitled) (Medico Legal Update, 2021)
Background: Nurse Interns face a wide range of hazards in hospitals including needle stick injuries, back injuries, latex allergy, violence, and stress. The goal of this study: Identify the impact of training program regarding occupational health hazards on nurse interns’ knowledge, practice and attitude through: assessing nurse interns’ knowledge regarding occupational health hazards before and after the program, assessing nurse interns’ practice regarding of occupational health hazards before and after the program,assessing nurse interns’ attitude regarding of occupational health hazards before and after the program, designing and implementing the training program and measuring the effect of training program regarding occupational health hazards on nurse interns’ knowledge and practice. Design: Quisi- experimental research design. Subject: The study was conducted at four hospitals affiliated to Ain Shams University. The subjects of this investigation included 91 nurse interns. Tools of data collection: Data were collected by using four tools namely: Needs assessment sheet, Self - administered Questionnaire, Observation Checklist, and attitude scale. Results: Highly significant differences of total occupational health hazards knowledge among nurse interns throughout program phases was observed. Nurse interns’ total practice regarding occupational health hazards was markedly increased throughout program phases. Highly significant difference in total attitude towards protection from hazards throughout the program phases was noticed. Conclusion: Implementation of the training program led to significant improvements in nurse interns’ knowledge, practice, and attitude regarding occupational health hazards. Recommendations: providing training program for nurse interns about occupational hazards and especially on protective measures, development and dissemination of policies and guidelines of safety practices, evaluation sheet of the nurse interns should include items related to occupational health hazards and compliance ways of protection, and further investigation might include factors affect reporting of occupational hazards.